ERICA: smoking prevalence in Brazilian adolescents - Valeska Carvalho Figueiredo; André Salem Szklo; Letícia Casado Costa; Maria Cristina C Kuschnir; Thiago Luiz Nogueira da Silva; Katia Vergetti Bloch; Moyses Szklo (Revista de Saúde Pública, 2016)
ABSTRACT OBJECTIVE To estimate the prevalences of tobacco use, tobacco experimentation, and frequent smoking among Brazilian adolescents. METHODS We evaluated participants of the cross-sectional, nation-wide, school-based Study of Cardiovascular Risks in Adolescents (ERICA), which included 12- to 17-year-old adolescents from municipalities of over 100 thousand inhabitants. The study sample had a clustered, stratified design and was representative of the whole country, its geographical regions, and all 27 state capitals. The information was obtained with self-administered questionnaires. Tobacco experimentation was defined as having tried cigarettes at least once in life. Adolescents who had smoked on at least one day over the previous 30 days were considered current cigarette smokers. Having smoked cigarettes for at least seven consecutive days was an indicator for regular consumption of tobacco. Considering the complex sampling design, prevalences and 95% confidence intervals were estimated according to sociodemographic and socio-environmental characteristics. RESULTS We evaluated 74,589 adolescents. Among these, 18.5% (95%CI 17.7-19.4) had smoked at least once in life, 5.7% (95%CI 5.3-6.2) smoked at the time of the research, and 2.5% (95%CI 2.2-2.8) smoked often. Adolescents aged 15 to 17 years had higher prevalences for all indicators than those aged 12 to 14 years. The prevalences did not differ significantly between sexes. The highest prevalences were found in the South region and the lowest ones, in the Northeast region. Regardless of sex, the prevalences were found to be higher for adolescents who had had paid jobs, who lived with only one parent, and who reported having been in contact with smokers either inside or outside their homes. Female public school adolescents were found to smoke more than the ones from private schools. CONCLUSIONS Tobacco use among adolescents is still a challenge. Intending to reduce the prevalence of tobacco use among young people, especially the ones under socioeconomic vulnerability conditions, Brazil must consolidate and increase effective public health care measures.